2015
DOI: 10.3109/1354750x.2015.1118547
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage oligomeric matrix protein and hyaluronic acid are sensitive serum biomarkers for early cartilage lesions in the knee joint

Abstract: The purpose of this study was to evaluate the relationship between five previously established serum osteoarthritis biomarkers and the severity of cartilage lesions in the knee. Cartilage damage (classified according to the Outerbridge scoring system) and serum concentrations of cartilage oligomeric matrix protein (COMP), collagen type II C-telopeptide (CTX-II), matrix metalloproteinase-3 (MMP-3), collagen type III N-propeptide, (PIIINP), and hyaluronic acid (HA) were determined in 79 patients who underwent kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Interestingly, no genes were found to be down‐regulated at all time points. Genes up‐regulated at all time points included extracellular matrix (ECM) components ( Fn1 , collagens 3, 5, and 6, Cthrc1 , Thbs3 ), matrix metabolic enzymes ( Mmp3 ) and Wnt signaling proteins ( Sfrp2 and Wisp2 ). In addition, it included ECM and cell adhesion proteins (SRPX2 and TNN) and a synovial fibroblast cell surface marker (THY1).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, no genes were found to be down‐regulated at all time points. Genes up‐regulated at all time points included extracellular matrix (ECM) components ( Fn1 , collagens 3, 5, and 6, Cthrc1 , Thbs3 ), matrix metabolic enzymes ( Mmp3 ) and Wnt signaling proteins ( Sfrp2 and Wisp2 ). In addition, it included ECM and cell adhesion proteins (SRPX2 and TNN) and a synovial fibroblast cell surface marker (THY1).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise gender differences were seen for uCTX-II, MMP-3, uCol2-1 NO 2 and sHA 45 . Cartilage damage and concentrations of sCOMP, sCTX-II, sMMP-3, sPIIINP, and sHA were determined in 79 patients who underwent knee arthroscopy or total knee replacement in a study by Jiao and colleagues 47 . PIIANP, serum CTX-II, HA and COMP were measured in this study, but only HA and COMP concentrations were found to be significantly higher in the knee OA patients with early signs of cartilage damage 47 .…”
Section: Clinical Validation Of Existing Oa Biomarkersmentioning
confidence: 99%
“…Cartilage damage and concentrations of sCOMP, sCTX-II, sMMP-3, sPIIINP, and sHA were determined in 79 patients who underwent knee arthroscopy or total knee replacement in a study by Jiao and colleagues 47 . PIIANP, serum CTX-II, HA and COMP were measured in this study, but only HA and COMP concentrations were found to be significantly higher in the knee OA patients with early signs of cartilage damage 47 . These results suggest that sCOMP and HA concentrations can be used to predict early cartilage lesions in the knee.…”
Section: Clinical Validation Of Existing Oa Biomarkersmentioning
confidence: 99%
“…During tissue turnover, molecular biomarkers of OA are derived from tissue matrices released into fluids (i.e., blood, urine, or synovial fluid) [15,16]. They reflect bone or cartilage turnover and synovial metabolism, and can be used as an assessment of pathophysiological processes [17,18].…”
Section: Introductionmentioning
confidence: 99%